نمذجة توزع الاجهادات الحرارية في الوصلات اللحامية (Latakia University Journal -Engineering Sciences Series, 2018)
In this study we are make the modeling and simulation by using finite element method by utilizing program (CATIA V5) to calculate thermal stresses in TIG Spot at different welding currents and different welding times. These results give better distribution for thermal compressive stresses through depth and diameter of spot weld and we compared this results with others worked in other programs. في هذه الدراسة تم إجراء نمذجة و محاكاة باستخدام طريقة العناصر المنتهية FEM على برنامجCATIA V5 لحساب توزع الاجهادات الحرارية في وصلة لحامية عند تيارات لحام متغيرة وأزمنة لحام مختلفة وأظهرت النتائج القيم التي يكون عندها أفضل توزع للإجهادات الحرارية خلال قطر وعمق منطقة اللحام حيث تم مقارنة النتائج التي تم الحصول عليها باستخدام برنامج CATIA V5 مع نتائج دراسات مرجعية في هذا المجال وباستخدام برامج مختلفة.